Social phobia among student university - Farhad Mahmood Ahmed; Maha Hassan Baker (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Social phobia is considered a psychological problem and negatively affects the life of the individual and society, which is negatively reflected in the individual's social relationships and leads to his lack of confidence in himself and others together and affects his psychological and social compatibility The problem of the current research highlights social phobia, which is negatively reflected on the psychological health and social relations of the individual. Also, the importance of the research lies in the impact of its variables with many important psychological variables such as self-confidence, psychological and social compatibility, positive thinking. The sample consisted of (432) male and female students in Erbil governorate for the academic year (2021-2022) and they were selected using the random stratified method and were divided according to (specialization, gender, marital status and school stage). The researcher relied to collect data from the research sample on the following: Development of a scale (Raulin & Wee 1994) to measure social phobia, and it consisted in its final form after completing the terms of validity and reliability of (26) items and two alternatives. In order to achieve the data, the researcher used the statistical package (SPSS) And the results were as follows: - High level of social phobia among the research sample - There are no statistically significant differences between (genders, stage, and marital status) in the social phobia variable - There are statistically significant differences between the specialization (scientific - human) in the social phobia variable in favor of the scientific specialization.